Source polarisation independent single-shot cross-polarised optical coherence tomography approaches: a comparison - Blessing, Katharina; Schirmer, Judith; Sharma, Gargi; Singh, Kanwarpal (Optics InfoBase Conference Papers, 2022)
We have developed several methods to realise a cross-polarised optical coherence tomography system that works independent of the polarisation state of the source. Here, we compare the performance of these approaches.
CRIS-Team Scopus Importer:2022-10-21